Dolabella‐3, 7, 18‐triene, the main constituent of the essential oil of the white lotus flower (Nymphaea lotus, Nymphaeaceae). (6th April 2016) - Pottier, Maud; Albuquerque, Bheatriz Nunes de Lima; Bezerra‐Silva, Patrícia Cristina; da Rocha, Suyana Karolyne Lino; Maia, Artur Campos Dália; Hallwass, Fernando; Navarro‐Vázquez, Armando; Navarro, Daniela Maria do Amaral Ferraz
Abstract: This is the first report on the chemical composition of the essential oil of the flowers of the white lotus ( Nymphaea lotus, Nymphaeaceae). The relative configuration of its main constituent, the diterpenoid dolabella‐3, 7, 18‐triene, was determined to be (1 R, 3 E, 7 E, 11 S, 12 S ) on the basis of DFT DP4 13 C‐NMR quantitative chemical shift analysis. Both the essential oil (LC50  < 50 ppm) and aqueous solution (55% larvae mortality in 50% (v/v) concentration) obtained through hydrodistillation extraction exhibited a satisfactory larvicidal effect against Aedes aegypti larvae. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This is the first report on the chemical composition of the essential oil of the flowers of the white lotus (Nymphaea lotus, Nymphaeaceae). The relative configuration of its main constituent, the diterpenoid dolabella‐3, 7, 18‐triene, was determined to be (1R, 3E, 7E, 11S, 12S) on the basis of DFT DP4 13C‐NMR quantitative chemical shift analysis. Both the essential oil (LC50<50 ppm) and aqueous solution (55% larvae mortality in 50% (v/v) concentration) obtained through hydrodistillation extraction exhibited a satisfactory larvicidal effect against Aedes aegypti larvae.